Functional Outcome of Lateral Extraarticular Tenodesis with Anterior Cruciate Ligament Reconstruction Using Modified Lemaire's Procedure: A Prospective Study - Varrdhaman H Dhariwal; Mathan C Kumar; Elayaraja Mani; Sukumaran S Subramanian (Journal of Orthopedics and Joint Surgery)
Aims and background: The standard arthroscopic intraarticular anterior cruciate ligament (ACL) reconstruction with various grafts and techniques has failure rates of up to 16%. Modified Lemaire's technique is one procedure done to reduce the rate of revision ACL surgeries by adding a tenodesis laterally, thereby reducing anterolateral laxity. This study has been done to analyze the functional outcome of modified Lemaire's procedure in a 2-year follow-up period. Materials and methods: A prospective outcome study involving 30 patients who underwent modified Lemaire's procedure with ACL reconstruction in the Department of Orthopedics in Stanley Medical College and Hospital, Chennai, Tamil Nadu, India, were followed up in 6 months, 1 year, and 2 years and their preoperative (pre-op) and postoperative (post-op) pivot shift score, Tegner–Lysholm scoring and International Knee Documentation Committee (IKDC) scoring were analyzed. Results: All 30 patients who have undergone modified Lemaire's procedure have improved post-op Tegner–Lysholm scores and IKDC scores and reduced pivot shift scores. A statistically significant difference in mean between pre-op Lysholm and at 6 months Lysholm, at 1- and 2-year Lysholm with a p-value of <0.05. Conclusion: Improved post-op Tegner–Lysholm scoring and IKDC scoring show that the modified Lemaire's technique is a good procedure to reduce the rate of revision ACL surgeries. This procedure also addresses the anterolateral deficiency by reducing the prevalence of pivot-shift. Clinical significance: By adding modified Lemaire's procedure to ACL reconstruction, we can augment the ACL reconstruction and reduce the anterolateral laxities in patients with high-grade pivot shift.